Influence of maternal region of birth on neonatal outcomes of babies born small - Young, Nicole E.; Davies‐Tuck, Miranda; Malhotra, Atul (Acta Paediatrica, 2021)
To compare neonatal outcomes of small for gestational age (SGA) infants born to South Asian (SA)-born women and Australian/New Zealand (ANZ)-born women. Retrospective cohort study at a hospital network in Australia. Maternal and neonatal data were collected for infants born SGA between 2013 and 2017 to SA- or ANZ-born women. Rates of perinatal mortality and neonatal morbidities were analysed between groups. A total of 1018 SA and 959 ANZ SGA infants were included. SA SGA babies were older (median [IQR] 39 [38-40] weeks) and heavier (2590 [2310-2780] grams) compared to ANZ SGA babies (38 [37-40] weeks and 2480 [2059-2740] grams; P < .001 for both). After adjustment for differences in demographics, SA SGA babies were 1.5 times more likely to develop hypothermia (CI: 1.16-1.88, P = .001), but 60% less likely to be born with a major congenital malformation (CI: 0.24-0.67, P = .001) and 36% less likely to need gavage feeding (CI: 0.43-0.93, P = .02) compared to ANZ SGA babies. Small for gestational age babies of SA-born women have different neonatal outcomes as compared to those born to ANZ-born women. Further research into influence of maternal region of birth on placental function, organogenesis and body composition of SGA babies is warranted.